A Collection of Anglo-Norman Councils - Brett, Martin (The journal of ecclesiastical history, 1975)
The purpose of this article is first to give some account of a short collection of Anglo-Norman councils of the eleventh century, then to suggest that one of these councils, hitherto unknown, represents the canons of a council held by archbishop Lanfranc in 1072, and lastly to offer a tentative explanation of why the whole collection came to be put together.